2022
DOI: 10.1111/jne.13125
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression changes in the brain of a Cushing's syndrome mouse model

Abstract: Excess glucocorticoid exposure affects emotional and cognitive brain functions. The extreme form, Cushing's syndrome, is adequately modelled in the AdKO 2.0 mouse, consequential to adrenocortical hypertrophy and hypercorticosteronemia. We previously reported that the AdKO 2.0 mouse brain undergoes volumetric changes that resemble closely those of Cushing's syndrome human patients, as well as changes in expression of glial related marker proteins. In the present work, the expression of genes related to glial an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 73 publications
(136 reference statements)
0
12
0
Order By: Relevance
“…For example, AdKO mice showed strongly induced expression of FKBP5 and, in the amygdala and hippocampus, CRH. 51,52 In particular, the latter may be directly linked to anxiety and hyperarousal. It will be interesting to see to what extent the changes in these mouse models will be reversible after adrenalectomy or treatment with, for example, GR antagonists.…”
Section: Evidence From Experimental Modelsmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, AdKO mice showed strongly induced expression of FKBP5 and, in the amygdala and hippocampus, CRH. 51,52 In particular, the latter may be directly linked to anxiety and hyperarousal. It will be interesting to see to what extent the changes in these mouse models will be reversible after adrenalectomy or treatment with, for example, GR antagonists.…”
Section: Evidence From Experimental Modelsmentioning
confidence: 99%
“…Overall, both neuronal and glia cell populations are affected by the chronic hypercortisolemia. 50,51 The extensive changes in oligodendrocyte markers suggest that white matter changes are the consequence of direct targeting of the GR in these cells, which indeed express high levels of GR. 52 Indeed, Sgk1 mRNA expression in oligodendrocytes is highly responsive to stress or circadian glucocorticoid peaks.…”
Section: Evidence From Experimental Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, we recently observed that the astrocyte-specific gene coding for aquaporin 4 (Aqp4) was strongly suppressed in the brains of the AdKO mouse model for Cushing's disease. 10 Aquaporin 4 is the limiting factor for the process of cleaning the brain via "glymphatic flow". 95 Moreover, chronic stress and dexamethasone were both shown to reduce glymphatic flow in the rat, in a GR-dependent manner.…”
Section: Neurodegeneration and Aquaporinmentioning
confidence: 99%